Relationship Between Subduction Erosion and the Up‐Dip Limit of the 2014 Mw 8.1 Iquique Earthquake. Issue 9 (4th May 2021) - Petersen, Florian; Lange, Dietrich; Ma, Bo; Grevemeyer, Ingo; Geersen, Jacob; Klaeschen, Dirk; Contreras‐Reyes, Eduardo; Barrientos, Sergio; Tréhu, Anne M.; Vera, Emilio; Kopp, Heidrun
Abstract: The aftershock distribution of the 2014 Mw 8.1 Iquique earthquake offshore northern Chile, identified from a long‐term deployment of ocean bottom seismometers installed eight months after the mainshock, in conjunction with seismic reflection imaging, provides insights into the processes regulating the updip limit of coseismic rupture propagation. Aftershocks updip of the mainshock hypocenter frequently occur in the upper plate and are associated with normal faults identified from seismic reflection data. We propose that aftershock seismicity near the plate boundary documents subduction erosion that removes mass from the base of the wedge and results in normal faulting in the upper plate. The combination of very little or no sediment accretion and subduction erosion over millions of years has resulted in a very weak and aseismic frontal wedge. Our observations thus link the shallow subduction zone seismicity to subduction erosion processes that control the evolution of the overriding plate. Plain Language Summary: To better understand the controls on shallow seismicity and subduction erosion following large subduction earthquakes, we use marine recordings of the Mw 8.1 2014 Iquique earthquake aftershocks and long‐offset multi‐channel seismic data. By comparing the aftershock locations and seismic imaging, we observe that most aftershocks occurred in the upper continental plate and abruptly stopped in the frontal forearc. The amplitude characteristics of upper‐crust reflections indicate a fractured and fluid‐filled outer forearc, which is associated with the absence of aftershocks. Large‐scale faulting, as evidenced by disrupted reflections in the seismic image, can be correlated to upper plate seismicity. We propose that the aftershocks updip of the main earthquake area reflect active subduction erosion processes. Key Points: We investigate structure and seismicity at the updip end of the 2014 Iquique earthquake rupture using amphibious seismic data Seismicity updip of the 2014 Iquique earthquake occurs over a broad range likely interpreted to be related to the basal erosion processes Coseismic stress changes and aftershocks activate extensional faulting of the upper plate and subduction erosion